No entorno da casa patriarcal : identidades femininas múltiplas na crônica de autoria feminina paranaense - Luiz, Fabiana Marques (2013)
This research analyzes the female identities in chronic published in Parana- Brazil since 1970. The objective is to comprehend the presentation manner from the modern women in agreement to the Feminism while social and politics movement, with its debates that enabled new views to the feminine authorship literature, as well as the woman role in the society. The research was methodologically shared into six parts: classification and collection reading; forms creation; character analyzes; form filling; grouping and quantitative data interpretation and qualitative analyzes, that looked for aspects not inserted by numbers, as ideological positions from where the discussions were built. Altogether 625 characters were investigated, distributed in sixteen collections. The conjecture from the Critical Feminist Theory, allowed the expansion of discussions around the hierarchy division between genres, about the prejudice fostered by social essentialists constructions, creating archetypes and marginalization of women s writing. This paper includes reflexions that mark the feminist thought and its recent approaches, as well as displacement and fragmentation of contemporary subjects, pointing ways to comprehend the representation of female identities under non essentialists optics. The results point to both reduplication of essentialists practices representation, and for the multiplicity of the female subject. The representations of the characters seem to follow a standard construction consisting of many similarities, which cause them to be characterized as subdued and evil figures, however, cannot override the desire for change and transgression that emanates from these authors, even if the means by which seek react the lead sometimes to ratify their condition subdued. Thus, even though in the disposal process of patriarchal practices, says Teresa de Lauretis (1994, p. 207-208), women are still with one foot in the patriarchal household , still victims of the symbolic power exercised by structures such as Church, Family, School and State, naturalize and ratify the nastiest forms of domination.